Chapter Le risorse documentarie dell'Istituto di Teoria e Tecniche dell'Informazione Giuridica del CNR per un'analisi di termini giuridici rilevanti: il caso di studio della parola «razza» - Cammelli, Antonio (Proceedings e report, 2021)
Part of public opinion believes that Article 3 of the Italian Constitution should be reformulated by eliminating the word "race", because of its historical meanings. Some jurists disagree with this opinion believing that this presence is still justified by the need to fight possible discrimination or to protect minority rights. Biologists have also entered the debate, asserting that this word cannot be used to refer to human races because there's no scientific basis for race. Cleared up any doubt about the origin of the term and the use that should be made of it, to contribute to today's debate, we have verified how this term was used in the language of law, using the terminological resources of the Institute of Legal Informatics and Judicial Systems (IGSG) - CNR databases.